Designing expanded carrier screening panels: results of a qualitative study with European geneticists. (November 2016) - Chokoshvili, Davit; Janssens, Sandra; Vears, Danya; Borry, Pascal
Aim: To explore the views of clinical and molecular geneticists on the inclusion of disorders and specific pathogenic mutations into expanded carrier screening (ECS) tests for reproductive purposes.Materials & methods: In-depth semistructured interviews were conducted with 16 European geneticists between April and September 2014.Results: All participants supported carrier screening for severe, childhood-onset autosomal recessive disorders with known natural history. Some participants were also in favor of screening for late-onset and X-linked disorders. Regarding selection of specific pathogenic mutations, our participants argued that ECS should include highly penetrant pathogenic mutations with known genotype–phenotype associations.Conclusion: This study highlights main challenges surrounding the development of ECS panels and offers suggestions for future research in this rapidly advancing field.